Research advances and application of pulsed electric field on proteins and peptides in food. (January 2021) - Zhang, Simin; Sun, Liangzi; Ju, Huapeng; Bao, Zhijie; Zeng, Xin-an; Lin, Songyi
Graphical abstract: Research advances and potential application of PEF on proteins and peptides were reviewed. Highlights: The application of PEF on food-borne proteins and peptides is summarized. The protein extraction efficiency can be improved by PEF technology. PEF technology has the ability to activate or inhibit endogenous enzymes for food preservation. PEF technology can improve the biological activity of various food-borne peptides. Mechanistic insights into effect of PEF on proteins and peptides were provided. Abstract: Proteins or peptides are essential nutrients required by the human body because some essential amino acids cannot be biosynthesized. In this context, food industry is urged to find method to meet the demands of high protein yield and high bioactive protein/peptide production. Pulsed electric fields (PEF) possess high potential and a promising future in the processing and activity performance enhancement of protein/peptides. PEF processing, as food preservation technology, has ongoing from laboratory and pilot plant scale level to the industrial level, however, there was a lack of knowledge on the effects of PEF on proteins and peptides. In the last few years, the increasing number of studies demonstrated that PEF processing is effective in extracting protein, inactivating most endogenous enzymes in foods, improving peptides' biological activities. We provide an overview of existing and potential applications of PEF on proteins and peptides in food and suggest that the change in structures and functions of proteins/ protein hydrolysates (food component proteins/peptides and enzymes) in PEF processing is receiving considerable attention and may provide a basis for elucidating influence mechanism of PEF processing on protein/peptides and for further improving its application accuracy and range, which thereby could become a key technology for protein-based foods in the future.